High-strength and high-plasticity soluble magnesium alloy and preparation method thereof

By adding specific elements and process treatment to soluble magnesium alloys, the microstructure with high strength and high plasticity is formed, and the existing soluble magnesium alloys are solved, and the high-performance soluble magnesium alloys are achieved suitable for industrial applications.

CN119710407APending Publication Date: 2025-03-28CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411734591.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing soluble magnesium alloys are used for temporary plugging of tools, such as poor plasticity, low strength, and fast dissolution speed, which limits their large-scale industrial application.

Method used

By adding elements such as Zn, Y, Ni, Cu, Zr, Ca, Sn and In, high-strength I and W phases are formed, grain boundary binding force is enhanced, dissolution rate is improved, and the microstructure and performance of the alloy is controlled through alloying, solidification, homogenization, extrusion and heat treatment processes.

Benefits of technology

It realizes high-strength, high plasticity and fast dissolution soluble magnesium alloys, improves the performance and processing performance of temporary plugging tools, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710407A_ABST
    Figure CN119710407A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength and high-plasticity soluble magnesium alloy and a preparation method thereof, belongs to the technical field of metal materials, and is used for solving at least one of the problems of poor plasticity, low strength, high dissolution speed and the like when the existing soluble magnesium alloy is used as a temporary plugging tool. According to the high-strength and high-plasticity soluble magnesium alloy, Zn and Y are added to form a high-strength I phase (Mg3Zn6Y) and a high-strength W phase (Mg12YZn), and the room-temperature strength and the high-temperature strength of the alloy are remarkably improved; and the grain boundary binding force is enhanced through existence of a proper amount of the I phase and the W phase, and the plasticity of the alloy is improved. According to the preparation method disclosed by the invention, the size, morphology, distribution and volume fraction of the phase I and the phase W can be controlled through process changes during alloying, solidification, homogenization, extrusion and heat treatment, so that synchronous improvement of the strength and plasticity of the soluble magnesium alloy is realized; by changing the contents of Cu and Ni elements and optimizing a solidification extrusion process, the number, size, morphology and distribution characteristics of the high-potential precipitated phases can be controlled, so that the dissolution rate of the soluble magnesium alloy is controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to a high-strength and high-plasticity soluble magnesium alloy and a preparation method thereof. Background Art

[0002] With the acceleration of energy structure transformation and the development of unconventional oil and gas resources, unconventional energy such as shale gas and tight oil and gas are gradually becoming an important part of global energy production. In the process of exploiting these resources, horizontal well segmented fracturing technology has become a key technology to improve oil and gas recovery and production. This technology requires the use of temporary plugging tools to isolate the well section in order to maintain the construction pressure and ensure the accuracy of the fracturing construction. However, traditional temporary plugging tools are usually made of steel, cast iron or composite materials, and need to be removed mechanically after fracturing is completed, which is not only time-consuming and labor-intensive, but also prone to problems such as stuck drill and blockage, increasing operating costs and risks.

[0003] As a new type of material, soluble magnesium alloy has gradually become an ideal choice for temporary plugging tools for staged fracturing due to its low density, high specific strength, good processing performance and fast dissolution rate. The soluble magnesium alloy temporary plugging tool can be removed by dissolution after the fracturing is completed, avoiding the complexity of traditional cleaning methods, greatly improving operation efficiency, reducing construction cycles, and reducing later maintenance costs. Therefore, the soluble magnesium alloy first needs to have high strength to ensure effective isolation between middle sections during fracturing construction, and needs to have a fast dissolution rate, so that it can dissolve quickly after the construction is completed without producing large pieces of residue, and subsequent oil production operations can be carried out quickly. However, the current series of high-strength soluble magnesium alloys have low plasticity (≤10%) and poor processing performance, which seriously limits the large-scale industrial application of soluble magnesium alloys. Summary of the invention

[0004] In view of the above analysis, the present invention aims to provide a high-strength and high-plasticity soluble magnesium alloy and a preparation method thereof, so as to solve at least one of the problems of the existing soluble magnesium alloys when used as temporary plugging tools, such as poor plasticity, low strength, and fast dissolution rate.

[0005] In a first aspect, the present invention provides a high-strength and high-plasticity soluble magnesium alloy, wherein the components of the high-strength and high-plasticity soluble magnesium alloy include, by mass percentage: Zn: 3-8%, Y: 0.5-2.5%, Ni: 0.1-2%, Cu: 0.1-2%, Zr: 0-0.5%, X: 0-2%, wherein Zn / Y>3, X is one of Ca, Sn, and In, and the remainder is Mg and unavoidable impurities.

[0006] Furthermore, the components of the high-strength and high-plasticity soluble magnesium alloy include, by mass percentage: Zn: 4-8%, Y: 1-2%, Ni: 0.2-0.5%, Cu: 0.5-1.5%, Zr: 0.2-0.4%, X: 0.5-1%.

[0007] Furthermore, Zn / Y is 4-6.

[0008] Furthermore, the microstructure of the high-strength and high-plasticity soluble magnesium alloy includes an α-Mg matrix, a Mg3Zn6Y quasi-crystalline phase, a Mg 12 YZn phase, MgZnCu phase and Mg2Ni phase, with a grain size of 5 to 30 μm.

[0009] Furthermore, the high-strength and high-plasticity soluble magnesium alloy has a tensile strength greater than 270 MPa, a yield strength greater than 180 MPa, an elongation greater than 14%, and a corrosion rate greater than 25 mg / cm2 in a 3% KCl solution at 93°C. 2 *h.

[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned high-strength and high-plasticity soluble magnesium alloy, comprising the following steps:

[0011] (1) Weigh each raw material according to mass percentage and set aside;

[0012] (2) Melting: After pure magnesium is melted under protective gas, the temperature is raised to 740-760°C, and pure zinc, Mg-Y master alloy, Mg-Ni master alloy or pure nickel, pure copper, Mg-Zr master alloy, Mg-X master alloy or pure X are added in sequence, stirred, and allowed to stand to obtain a melt;

[0013] (3) Casting: Cooling the melt to 720-740° C. for casting;

[0014] (4) Homogenization treatment: The alloy is homogenized at 400-450°C for 10-30 hours;

[0015] (5) Hot extrusion: hot extrusion of the homogenized ingot;

[0016] (6) The hot extruded bar is subjected to a solution aging treatment to obtain the high-strength and high-plasticity soluble magnesium alloy.

[0017] Furthermore, in step (2), when the total content of Ni and Cu in the melt is greater than 2%, electromagnetic stirring is added to the melt at a stirring speed of 200 to 300 rpm.

[0018] Furthermore, in step (3), the casting is mold casting or semi-continuous casting.

[0019] Furthermore, in step (5), the extrusion speed during the hot extrusion is 0.1 to 3 m / min, the extrusion temperature is 250 to 400° C., and the extrusion ratio is 10 to 40:1.

[0020] Furthermore, in step (6), the solution temperature is 420-500°C, the time is 5-10 h, and the aging time is 150-250°C, the time is 1-50 h.

[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0022] (1) The high-strength and high-plasticity soluble magnesium alloy of the present invention forms high-strength I phase (Mg3Zn6Y) and W phase (Mg 12 The room temperature and high temperature strength of the alloy are significantly improved by adding Y, In and Sn. The grain boundary bonding force is enhanced by the presence of appropriate amounts of I phase and W phase, thereby improving the plasticity of the alloy. The potential difference between the matrix and the second phase is enhanced by adding highly electrochemically active elements such as Zn, Cu, and Ni, and high potential precipitation phases such as MgZnCu and Mg2Ni are precipitated in the magnesium alloy, thereby significantly improving the dissolution rate of the magnesium alloy. The driving force of galvanic corrosion is increased by adding Ca, Sn and In elements, which effectively improves the overall dissolution rate of the alloy. The fluidity of the melt is improved by adding Y, In and Sn, casting defects (such as pores, segregation and hot cracks) are reduced, and the quality of castings is significantly improved. The grain structure of the alloy is refined by adding Zr, Ca and Cu elements, the distribution of the second phase during solidification is improved, and the strength and plasticity of the alloy are improved. The dynamic recrystallization behavior is improved by adding Sn and Ca elements, the deformation resistance during hot working is reduced, and the processing performance is significantly optimized.

[0023] (2) The preparation method of the present invention can control the size, morphology, distribution and volume fraction of the I phase and the W phase through process changes during alloying, solidification, homogenization, extrusion and heat treatment, thereby achieving a simultaneous improvement in the strength and plasticity of the soluble magnesium alloy; by changing the content of Cu and Ni elements and optimizing the solidification extrusion process, the number, size, morphology and distribution characteristics of these high-potential precipitated phases can be controlled, thereby controlling the dissolution rate of the soluble magnesium alloy;

[0024] (3) The high-strength and high-plasticity soluble magnesium alloy of the present invention has a tensile strength greater than 270 MPa, for example, a tensile strength of 270 to 380 MPa, a yield strength greater than 180 MPa, for example, a yield strength of 180 to 250 MPa, an elongation greater than 14%, for example, an elongation of 14 to 30%, and a corrosion rate greater than 25 mg / cm in a 3% KCl solution at 93°C. 2 *h, for example, 25-150 mg / cm 2 *h.

[0025] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0027] Figure 1 The microstructure diagram of the high-strength and high-plasticity soluble magnesium alloy prepared in Example 1 of the present invention;

[0028] Figure 2 This is a SEM image of the high-strength and high-plasticity soluble magnesium alloy prepared in Example 1 of the present invention;

[0029] Figure 3 This is a physical picture of the alloy prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0031] A specific embodiment of the present invention discloses a high-strength and high-plasticity soluble magnesium alloy, wherein the components of the high-strength and high-plasticity soluble magnesium alloy include, by mass percentage, Zn: 3-8%, Y: 0.5-2.5%, Ni: 0.1-2%, Cu: 0.1-2%, Zr: 0-0.5%, X: 0-2%, wherein Zn / Y>3, X is one of Ca, Sn, and In, and the remainder is Mg and unavoidable impurities.

[0032] The following is a detailed description of the effects and dosage of the components in the present invention:

[0033] Zn: Zn is the main strengthening element in the soluble magnesium alloy of the present invention. The maximum saturated solid solubility of Zn in Mg is 6.2%. It can hinder the movement of dislocations through the lattice distortion effect, thereby significantly improving the strength of the alloy. Zn and Y together form I phase (Mg3Zn6Y quasi-crystal phase) and W phase (Mg 12YZn), these two phases can effectively pin dislocations and refine grains, further improving the strength and hardness of the alloy; in addition, the high electrochemical activity of Zn will increase the potential difference with the matrix, enhance the driving force of local corrosion, and accelerate the dissolution process of the alloy. If the Zn content is too low, it may lead to insufficient formation of the strengthening phase (I phase or W phase), affecting the strength and hardness. If the Zn content is too high, it is easy to generate a brittle phase (such as Mg-Zn compounds), reducing plasticity and toughness. Therefore, the Zn content in the present invention is controlled at 3-8%, for example, 3%, 4%, 5%, 6%, 7%, 8%.

[0034] Y: The solubility of Y in the Mg matrix is ​​low, but the Y atoms dissolved in the matrix can cause lattice distortion, thereby producing a pinning effect on dislocations and enhancing the matrix strength; Y and Zn together form a high-strength second phase (such as I phase and W phase), which improves the room temperature and high temperature strength of the alloy; the addition of Y changes the solidification behavior of the alloy, which can refine the grains, reduce component segregation, reduce the hot cracking sensitivity of the alloy, and improve the quality of the ingot. If the Y content is too low, it may lead to insufficient formation of the strengthening phase (I phase or W phase), affecting the strength and hardness. If the Y content is too high, it may form too many W phases or coarse I phase clusters, reducing plasticity and dissolution uniformity, while increasing the brittleness of the material. Therefore, the Y content in the present invention is controlled at 0.5-2.5%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%.

[0035] Combined addition of Zn and Y: Combined addition of Zn and Y can form I phase (Mg3Zn6Y quasi-crystalline phase) and W phase (Mg 12 YZn), and the weight of the precipitated phase is related to the Zn / Y ratio. When Zn / Y is 3, only W phase is formed in the alloy, and when Zn / Y is 6, only I phase is formed in the alloy. I phase is a stable phase of quasi-crystalline structure, has high strength and excellent thermal stability, and can significantly improve the strength of the alloy, but too much I phase (when it is agglomerated or network distributed) will reduce the plasticity of the alloy; W phase is a solid solution phase of FCC structure, which has low strength itself and has little effect on strength, but its distribution on the grain boundary enhances the bonding force of the grain boundary and improves the plasticity and toughness of the alloy. Therefore, in the present invention, the Zn / Y ratio is preferably selected to be 4 to 6, for example, 4, 4.5, 5, 5.5, 6 (Zn: 4 to 8%, Y: 1 to 2%).

[0036] Ni: Ni and Mg generate a brittle Mg2Ni phase, whose high hardness and thermal stability can significantly improve the room temperature and high temperature strength of the alloy. At the same time, the Mg2Ni phase has a high electrochemical potential, which can accelerate the dissolution rate of the alloy, but too much can easily reduce the plasticity of the alloy. Therefore, the Ni content in the present invention is controlled at 0.1-2% (preferably 0.2-0.5%).

[0037] Cu: The addition of Cu element can optimize the cast structure of Mg-Zn-Y-Zr alloy, refine the primary α-Mg grains, and transform the coarse dendritic grains into fine equiaxed grains. At the same time, Cu and Zn work together to form a network-distributed eutectic structure between dendrites and grain boundaries, including I phase (Mg3Zn6Y quasi-crystalline phase) and newly generated MgZnCu (Laves phase). The addition of Laves phase not only improves the structural stability of the alloy, but also enhances the inhibitory effect on grain growth, thereby further refining the structure. Due to the grain refinement caused by Cu element and the joint strengthening effect of the network-distributed I phase and Laves phase, the room temperature and high temperature mechanical properties of Mg-Zn-Y-Zr alloy can be improved. In addition, since the electrochemical potential of the Laves phase is much higher than that of the α-Mg matrix, the segregation of Cu exacerbates the potential difference between the matrix and the second phase, enhances the driving force of microgalvanic corrosion, and the continuous network distribution of the Laves phase may exacerbate the local corrosion at the grain boundary, so Cu can significantly increase the dissolution rate of the magnesium alloy. However, in order to prevent excessive addition of Cu elements to form coarse MgZnCu (Laves phase) and affect the plastic deformation ability of the magnesium alloy, the content of Cu in the present invention is controlled at 0.1-2%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% (preferably 0.5-1.5%).

[0038] Zr: The main purpose of adding Zr is to refine the grains, thereby reducing the tendency of hot cracking, improving casting properties, and increasing the strength of the alloy. Zr only acts as a heterogeneous nucleation core to refine the grains during solidification, and does not form compounds in the Mg-Zn-Y alloy. Therefore, the Zr content in the present invention is controlled at 0-0.5%, for example, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% (preferably 0.4%).

[0039] Ca: Ca can effectively refine the grains by enriching at the front of the solid-liquid interface, and can reduce the size and agglomeration of the second phase (such as I phase or W phase), making its distribution more uniform, thereby improving the consistency of material properties. Ca (> 0.5%) forms a Ca2Mg6Zn3 low-melting-point phase with Zn and Mg, which is mainly distributed at the grain boundary and can significantly enhance the grain boundary bonding force, improve the tensile strength and yield strength of the alloy, but too much will lead to a decrease in alloy plasticity and increase crack sensitivity; the Ca2Mg6Zn3 phase can be used as a sacrificial phase during the dissolution process to increase the dissolution rate of the alloy; therefore, the Ca content in the present invention is controlled at 0-2%, for example, 0%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2% (preferably 1%).

[0040] Sn: Sn can reduce casting defects and improve dynamic recrystallization behavior, thereby improving the processing properties of the alloy; Sn can significantly improve strength through solid solution strengthening and precipitation strengthening (Mg2Sn), while grain refinement improves plasticity and toughness; Sn has a low standard electrode potential, and its addition significantly increases the potential difference between the matrix and the second phase, enhances microgalvanic corrosion, and improves the dissolution rate of the alloy. Therefore, the Sn content in the present invention is controlled at 0-2%, for example, 0%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2% (preferably 1%).

[0041] In: The addition of In improves melt fluidity and reduces casting defects (such as pores and segregation); In is a highly electronegative element and is easily segregated to the grain boundary or the second phase, significantly increasing the driving force of galvanic corrosion and accelerating the dissolution of the alloy. Therefore, the In content in the present invention is controlled at 0-2%, for example, 0%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2% (preferably 0.5%).

[0042] The high-strength and high-plasticity soluble magnesium alloy of the present invention forms high-strength I phase (Mg3Zn6Y) and W phase (Mg 12The room temperature and high temperature strength of the alloy are significantly improved by adding Y, In and Sn. The grain boundary bonding force is enhanced by the presence of appropriate amounts of I phase and W phase, thereby improving the plasticity of the alloy. The potential difference between the matrix and the second phase is enhanced by adding highly electrochemically active elements such as Zn, Cu, and Ni, and high potential precipitation phases such as MgZnCu and Mg2Ni are precipitated in the magnesium alloy, thereby significantly improving the dissolution rate of the magnesium alloy. The driving force of galvanic corrosion is increased by adding Ca, Sn and In elements, which effectively improves the overall dissolution rate of the alloy. The fluidity of the melt is improved by adding Y, In and Sn, casting defects (such as pores, segregation and hot cracks) are reduced, and the quality of castings is significantly improved. The grain structure of the alloy is refined by adding Zr, Ca and Cu elements, the distribution of the second phase during solidification is improved, and the strength and plasticity of the alloy are improved. The dynamic recrystallization behavior is improved by adding Sn and Ca elements, the deformation resistance during hot working is reduced, and the processing performance is significantly optimized.

[0043] Specifically, the components of the high-strength and high-plasticity soluble magnesium alloy include, by mass percentage: Zn: 4-8%, Y: 1-2%, Ni: 0.2-0.5%, Cu: 0.5-1.5%, Zr: 0.2-0.4%, and X: 0.5-1%.

[0044] Specifically, Zn / Y is 4 to 6. When the Zn / Y content is within the above range, the strength, plasticity and solubility of the alloy are good.

[0045] Specifically, the microstructure of the high-strength and high-plasticity soluble magnesium alloy includes an α-Mg matrix, a Mg3Zn6Y quasi-crystalline phase, and a Mg 12 YZn phase, MgZnCu phase and Mg2Ni phase have a grain size of 5 to 30μm, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, and 30μm.

[0046] Specifically, the high-strength and high-plasticity soluble magnesium alloy has a tensile strength greater than 270 MPa, for example, a tensile strength of 270 to 380 MPa, a yield strength greater than 180 MPa, for example, a yield strength of 180 to 250 MPa, an elongation greater than 14%, for example, an elongation of 14 to 30%, and a corrosion rate greater than 25 mg / cm in a 3% KCl solution at 93°C. 2 *h, for example, 25-150 mg / cm 2 *h.

[0047] Another specific embodiment of the present invention discloses a method for preparing a high-strength and high-plasticity soluble magnesium alloy, comprising the following steps:

[0048] (1) Weigh each raw material according to mass percentage and set aside;

[0049] (2) Melting: After pure magnesium is melted under protective gas, the temperature is raised to 740-760°C, and pure zinc, Mg-Y master alloy, Mg-Ni master alloy or pure nickel, pure copper, Mg-Zr master alloy, Mg-X master alloy or pure X are added in sequence, stirred, and allowed to stand to obtain a melt;

[0050] (3) Casting: Cooling the melt to 720-740° C. for casting;

[0051] (4) Homogenization treatment: The alloy is homogenized at 400-450°C for 10-30 hours to eliminate segregation in the alloy;

[0052] (5) Hot extrusion: hot extrusion of the homogenized ingot;

[0053] (6) The hot extruded bar is subjected to a solution aging treatment to obtain the high-strength and high-plasticity soluble magnesium alloy.

[0054] Specifically, in step (1), the raw material needs to be pretreated, and the pretreatment is to clean the oxide layer on the surface of the raw material with sandpaper, put the treated metal raw material into a drying box, and dry it at 200° C. for 2 to 4 hours to remove surface moisture and impurities.

[0055] Specifically, in step (2), when the total content of Ni and Cu in the melt is greater than 2%, electromagnetic stirring is added to the melt, and the stirring speed is 200-300 rpm, for example, 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm, 300 rpm.

[0056] It should be noted that the protective gas is a mixture of SF6 and CO2. During smelting, the crucible is first heated to 720°C at a heating rate of 20°C / min, pure magnesium is first put into the crucible for melting, and after the pure magnesium is melted, the temperature is raised to 760°C, and pure zinc, Mg-Y master alloy, Mg-Ni master alloy or pure nickel, pure copper, Mg-Zr master alloy are added in sequence, stirred for 10 minutes to ensure uniform alloy composition, and then allowed to stand for 10 to 20 minutes to remove inclusions on the surface of the melt. When the total content of Ni and Cu in the melt is greater than 2%, electromagnetic stirring is performed in the melt at a stirring speed of 200 to 300 rpm.

[0057] Specifically, in step (3), the casting is die casting or semi-continuous casting.

[0058] It should be noted that in order to reduce casting defects such as pores and thermal cracks during die casting, the mold can be preheated at 200-250° C. During semi-continuous casting, the continuous casting speed is 10-70 mm / min.

[0059] Specifically, in step (5), the extrusion speed during hot extrusion is 0.1 to 3 m / min, for example, 0.1 m / min, 0.5 m / min, 1.0 m / min, 1.5 m / min, 2.0 m / min, 2.5 m / min, 3 m / min, and the extrusion temperature is 250 to 400°C, for example, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, ℃, 330℃, 340℃, 350℃, 360℃, 370℃, 380℃, 390℃, 400℃, and the extrusion ratio is 10-40:1, for example, 10:1, 12:1, 14:1, 16:1, 18:1, 20:1, 22:1, 24:1, 26:1, 28:1, 30:1, 32:1, 34:1, 36:1, 38:1, 40:1, and molybdenum disulfide is used as a lubricant during the extrusion process.

[0060] Specifically, in step (6), the solution temperature is 420-500°C, for example, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, and the time is 5-10h, for example, 5h, 6h, 7h, 8h, 9h, 10h, and the aging time is 150-250°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, and the time is 1-50h, for example, 1h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 50h.

[0061] The soluble magnesium alloy of the patent of the present invention has both high strength and high plasticity, a fast and uniformly controllable dissolution rate, excellent casting and processing properties, can meet the needs of temporary plugging tools used in special fields such as shale gas extraction, and is suitable for industrial large-scale production.

[0062] The preparation method of the present invention can control the size, morphology, distribution and volume fraction of the I phase and the W phase through process changes during alloying, solidification, homogenization, extrusion and heat treatment, thereby achieving a simultaneous improvement in the strength and plasticity of the soluble magnesium alloy; by changing the Cu and Ni element contents and optimizing the solidification extrusion process, the number, size, morphology and distribution characteristics of these high-potential precipitated phases can be controlled, thereby controlling the dissolution rate of the soluble magnesium alloy.

[0063] The technical solution of the present invention is further explained below in conjunction with the following specific embodiments.

[0064] The chemical compositions and contents in the following examples and comparative examples are shown in Table 1.

[0065] Example 1

[0066] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0067] (1) Raw material processing: Weigh the required raw materials according to the weight percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200℃ for 2 to 4 hours to remove surface moisture and impurities.

[0068] (2) Melting: Heat the crucible to 720℃ at a heating rate of 20℃ / min, put pure magnesium into the crucible first, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760℃, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, and finally Mg-Zr master alloy. Stir for 10 minutes to ensure uniform alloy composition, and then let it stand for 10 to 20 minutes.

[0069] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0070] (4) Homogenization treatment: The homogenization condition of the alloy is 400℃×20h.

[0071] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 2.5 m / min, a temperature of 300 °C, an extrusion ratio of 30:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0072] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is 500°C × 2h and the aging treatment is 200°C × 24h.

[0073] The microstructure of the alloy prepared in Example 1 is shown in Figure 1 As shown in the SEM images Figure 2 shown.

[0074] Example 2

[0075] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0076] (1) Raw material processing: Weigh the required raw materials according to the mass percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200°C for 2 to 4 hours to remove surface moisture and impurities.

[0077] (2) Melting: Heat the crucible to 720℃ at a heating rate of 20℃ / min, put pure magnesium into the crucible first, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760℃, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, and finally Mg-Zr master alloy. Stir for 10 minutes to ensure uniform alloy composition, and then let it stand for 10 to 20 minutes.

[0078] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0079] (4) Homogenization treatment: The homogenization condition of the alloy is 400℃×20h.

[0080] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 0.5 m / min, a temperature of 330 °C, an extrusion ratio of 40:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0081] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is at 470°C for 5 h and the aging treatment is at 180°C for 20 h.

[0082] Example 3

[0083] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0084] (1) Raw material processing: Weigh the required raw materials according to the weight percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200℃ for 2 to 4 hours to remove surface moisture and impurities.

[0085] (2) Melting: Heat the crucible to 720°C at a heating rate of 20°C / min, first put pure magnesium into the crucible, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760°C, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, and finally Mg-Zr master alloy. Perform electromagnetic stirring in the melt for 20 minutes at a stirring speed of 200-300rpm;

[0086] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0087] (4) Homogenization treatment: The homogenization condition of the alloy is 420℃×20h.

[0088] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 0.5 m / min, a temperature of 400 °C, an extrusion ratio of 22:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0089] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is at 470°C for 5 h and the aging treatment is at 200°C for 24 h.

[0090] Example 4

[0091] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0092] (1) Raw material processing: Weigh the required raw materials according to the weight percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200℃ for 2 to 4 hours to remove surface moisture and impurities.

[0093] (2) Melting: Heat the crucible to 720℃ at a heating rate of 20℃ / min, put pure magnesium into the crucible first, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760℃, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, and finally Mg-Zr master alloy. Stir for 10 minutes to ensure uniform alloy composition, and then let it stand for 10 to 20 minutes.

[0094] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0095] (4) Homogenization treatment: The homogenization condition of the alloy is 400℃×20h.

[0096] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 0.5 m / min, a temperature of 330 °C, an extrusion ratio of 30:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0097] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is at 470°C for 5 h and the aging treatment is at 200°C for 18 h.

[0098] Example 5

[0099] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0100] (1) Raw material processing: Weigh the required raw materials according to the weight percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200℃ for 2 to 4 hours to remove surface moisture and impurities.

[0101] (2) Melting: Heat the crucible to 720°C at a heating rate of 20°C / min, first put pure magnesium into the crucible, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760°C, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, and finally Mg-Zr master alloy. Perform electromagnetic stirring in the melt for 20 minutes at a stirring speed of 200-300rpm;

[0102] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0103] (4) Homogenization treatment: The homogenization condition of the alloy is 430℃×20h.

[0104] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 0.5 m / min, a temperature of 400 °C, an extrusion ratio of 12:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0105] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is 500°C × 5h and the aging treatment is 240°C × 35h.

[0106] Example 6

[0107] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0108] (1) Raw material processing: Weigh the required raw materials according to the weight percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200℃ for 2 to 4 hours to remove surface moisture and impurities.

[0109] (2) Melting: Heat the crucible to 720℃ at a heating rate of 20℃ / min, put pure magnesium into the crucible first, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760℃, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, and finally Mg-Zr master alloy. Stir for 10 minutes to ensure uniform alloy composition, and then let it stand for 10 to 20 minutes.

[0110] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0111] (4) Homogenization treatment: The homogenization condition of the alloy is 400℃×20h.

[0112] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 1 m / min, a temperature of 300 °C, an extrusion ratio of 16:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0113] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is at 470°C for 5 h and the aging treatment is at 200°C for 24 h.

[0114] Example 7

[0115] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0116] (1) Raw material processing: Weigh the required raw materials (such as pure magnesium, pure zinc, Mg-Y master alloy, Mg-Zr master alloy) according to the weight percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200°C for 2 to 4 hours to remove surface moisture and impurities.

[0117] (2) Melting: Heat the crucible to 720℃ at a heating rate of 20℃ / min, put pure magnesium into the crucible first, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760℃, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, and finally Mg-Zr master alloy. Stir for 10 minutes to ensure uniform alloy composition, and then let it stand for 10 to 20 minutes.

[0118] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0119] (4) Homogenization treatment: The homogenization condition of the alloy is 420℃×20h.

[0120] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 0.5 m / min, a temperature of 400 °C, an extrusion ratio of 20:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0121] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is at 470°C for 5 h and the aging treatment is at 200°C for 24 h.

[0122] Example 8

[0123] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0124] (1) Raw material processing: Weigh the required raw materials according to the weight percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200℃ for 2 to 4 hours to remove surface moisture and impurities.

[0125] (2) Melting: Heat the crucible to 720°C at a heating rate of 20°C / min, first put pure magnesium into the crucible, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760°C, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, Mg-Zr master alloy, and Mg-Ca master alloy. Stir for 10 minutes to ensure that the alloy composition is uniform, and then let it stand for 10 to 20 minutes.

[0126] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0127] (4) Homogenization treatment: The homogenization condition of the alloy is 400℃×20h.

[0128] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 0.5 m / min, a temperature of 330 °C, an extrusion ratio of 25:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0129] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is at 470°C for 5 h and the aging treatment is at 200°C for 24 h.

[0130] Example 9

[0131] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0132] (1) Raw material processing: Weigh the required raw materials according to the weight percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200℃ for 2 to 4 hours to remove surface moisture and impurities.

[0133] (2) Melting: Heat the crucible to 720°C at a heating rate of 20°C / min, first put pure magnesium into the crucible, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760°C, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, Mg-Zr master alloy, and pure Sn. Stir for 10 minutes to ensure uniform alloy composition, and then let it stand for 10 to 20 minutes.

[0134] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0135] (4) Homogenization treatment: The homogenization condition of the alloy is 400℃×20h.

[0136] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 0.5 m / min, a temperature of 330 °C, an extrusion ratio of 30:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0137] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is at 470°C for 5 h and the aging treatment is at 200°C for 24 h.

[0138] Example 10

[0139] A method for preparing a high-strength and high-plasticity soluble magnesium alloy in this embodiment comprises the following steps:

[0140] (1) Raw material processing: Weigh the required raw materials according to the weight percentage, and use sandpaper to clean the oxide layer on the surface of the raw materials. Put the treated metal raw materials into a drying oven and dry them at 200℃ for 2 to 4 hours to remove surface moisture and impurities.

[0141] (2) Melting: Heat the crucible to 720°C at a heating rate of 20°C / min, first put pure magnesium into the crucible, and use a mixed gas of SF6 and CO2 to protect the melt during the melting process. After all the pure magnesium is melted, raise the temperature to 760°C, and gradually add pure zinc, Mg-Y master alloy, Mg-Cu master alloy, Mg-Ni master alloy, Mg-Zr master alloy, and pure In. Stir for 10 minutes to ensure uniform alloy composition, and then let it stand for 10 to 20 minutes.

[0142] (3) Casting: After the melt temperature is reduced to 720-740°C, mold casting is performed and the mold is preheated at 200-250°C.

[0143] (4) Homogenization treatment: The homogenization condition of the alloy is 400℃×20h.

[0144] (5) Hot extrusion: The homogenized ingot was hot extruded at a speed of 0.5 m / min, a temperature of 300 °C, an extrusion ratio of 25:1, and molybdenum disulfide was used as a lubricant during the extrusion process.

[0145] (6) Heat treatment: The extruded soluble magnesium alloy rod is subjected to solution aging treatment. The solution treatment is at 470°C for 5 h and the aging treatment is at 200°C for 24 h.

[0146] Embodiment 11

[0147] The preparation method of the high-strength and high-plasticity soluble magnesium alloy in this embodiment is the same as that in Embodiment 1, except for the components, as shown in Table 1.

[0148] Example 12

[0149] The preparation method of the high-strength and high-plasticity soluble magnesium alloy in this embodiment is the same as that in Embodiment 1, except for the components, as shown in Table 1.

[0150] Embodiment 13

[0151] The preparation method of the high-strength and high-plasticity soluble magnesium alloy in this embodiment is the same as that in Embodiment 8, except for the components, as shown in Table 1.

[0152] Comparative Example 1

[0153] The preparation method of the high-strength and high-plasticity soluble magnesium alloy in this comparative example is the same as that in Example 1, except for the components, as shown in Table 1.

[0154] Comparative Example 2

[0155] The preparation method of the high-strength and high-plasticity soluble magnesium alloy in this comparative example is the same as that in Example 1, except for the components, as shown in Table 1.

[0156] Comparative Example 3

[0157] The preparation method of the high-strength and high-plasticity soluble magnesium alloy in this comparative example is the same as that in Example 1, except for the components, as shown in Table 1.

[0158] Comparative Example 4

[0159] The preparation method of the high-strength and high-plasticity soluble magnesium alloy in this comparative example is the same as that in Example 1, except for the components, as shown in Table 1.

[0160] Comparative Example 5

[0161] The components of the high-strength and high-plasticity soluble magnesium alloy in this comparative example are the same as those in Example 1, except that the preparation method is different. Specifically, in step (5), the extrusion speed during hot extrusion is 3.5 m / min, the extrusion temperature is 350°C, and the extrusion ratio is 45:1. Under this process, the surface of the magnesium alloy casting cracks after extrusion. Figure 3 shown.

[0162] Table 1 Chemical compositions of the embodiments and comparative examples

[0163] Group Mg Zn Y Cu Ni Zr X Zn / Y Example 1 Bal. 4.8 1.2 0.5 0.5 0.4 0 4 Example 2 Bal. 4 1 0.2 0.2 0.4 0 4 Example 3 Bal. 4.8 1.2 1.5 0.5 0.4 0 4 Example 4 Bal. 6 1 1 0.5 0.4 0 6 Example 5 Bal. 6 1 1.5 1.5 0.4 0 6 Example 6 Bal. 6 1.5 1 0.5 0.4 0 4 Example 7 Bal. 8 2 1 0.5 0.4 0 4 Example 8 Bal. 6 1 0.5 0.5 0.4 1(Ca) 6 Example 9 Bal. 6 1 0.5 0.5 0.4 1(Sn) 6 Example 10 Bal. 6 1 0.5 0.5 0.4 0.5(In) 6 Embodiment 11 Bal. 4 1 0.2 0.2 0 0 4 Example 12 Bal. 3 0.5 2 2 0.5 0 6 Embodiment 13 Bal. 6 1 1 0.5 0.4 1(Ca) 6 Comparative Example 1 Bal. 4 2 0.5 0.5 0.4 0 2 Comparative Example 2 Bal. 10 0.4 0.5 0.5 0.4 0 25 Comparative Example 3 Bal. 4.8 1.2 0 0.5 0.4 0 4 Comparative Example 4 Bal. 4.8 1.2 0.5 0 0.4 0 4 Comparative Example 5 Bal. 4.8 1.2 0.5 0.5 0.4 0 4

[0164] Test Example 1

[0165] The properties and microstructures of the alloys of Examples 1-13 and Comparative Examples 1-5 were tested respectively, and the structures are shown in Table 2.

[0166] Table 2

[0167]

[0168] According to Examples 1 to 13, when Zn / Y is 4 to 6, the alloy has the characteristics of high strength and high plasticity. Although the composition of Comparative Example 1 is within the scope of this patent, since Zn / Y is 2, there is no I phase in its structure, and it is Mg7Zn3 phase and W phase, and the W phase content is too high and the size is large, which will lead to a significant decrease in plasticity. In Comparative Example 2, the Zn content is higher and the Y content is lower. The alloy mainly forms MgZn2 and Mg7Zn3 phases. The pinning effect of these two relative dislocations is weaker than that of the I phase, and the Mg7Zn3 phase is often distributed at the grain boundaries, which may weaken the grain boundary strength and plasticity. Therefore, the strength and plasticity of the alloy in Comparative Example 2 are both reduced. Comparative Examples 3 and 4 add Ni or Cu elements alone, and their dissolution rate is lower than that of the alloys to which Ni and Cu are added at the same time. Due to the excessive extrusion ratio and the excessively fast extrusion speed, a large number of extrusion cracks are generated on the surface of the rod after extrusion in Comparative Example 5, and the processing fails.

[0169] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A high-strength, high-plasticity soluble magnesium alloy, characterized in that: The components of the high-strength and high-plasticity soluble magnesium alloy include, by mass percentage, Zn: 3-8%, Y: 0.5-2.5%, Ni: 0.1-2%, Cu: 0.1-2%, Zr: 0-0.5%, X: 0-2%, wherein Zn / Y>3, X is one of Ca, Sn, In, and the remainder is Mg and unavoidable impurities.

2. A high-strength, high-plasticity soluble magnesium alloy according to claim 1, characterized in that: The components of the high-strength and high-plasticity soluble magnesium alloy include, by mass percentage, Zn: 4-8%, Y: 1-2%, Ni: 0.2-0.5%, Cu: 0.5-1.5%, Zr: 0.2-0.4%, and X: 0.5-1%.

3. A high-strength, high-plasticity soluble magnesium alloy according to claim 1 or 2, characterized in that: Zn / Y is 4~6.

4. A high-strength, high-plasticity soluble magnesium alloy according to claim 1 or 2, characterized in that: The high-strength and high-plasticity soluble magnesium alloy microstructure includes an α-Mg matrix, a Mg3Zn6Y quasi-crystal phase, and a Mg 12 YZn phase, MgZnCu phase and Mg2Ni phase, with a grain size of 5 to 30 μm.

5. A high-strength, high-plasticity soluble magnesium alloy according to claim 1 or 2, characterized in that: The tensile strength of the high-strength and high-plasticity soluble magnesium alloy is greater than 270MPa, the yield strength is greater than 180MPa, the elongation is greater than 14%, and the corrosion rate in 93°C, 3% KCl solution is greater than 25mg / cm 2 *h.

6. A method for preparing a high-strength and high-plasticity soluble magnesium alloy according to any one of claims 1 to 5, characterized in that: The steps include: (1) Weigh each raw material according to mass percentage and set aside; (2) Melting: After pure magnesium is melted under protective gas, the temperature is raised to 740-760°C, and pure zinc, Mg-Y master alloy, Mg-Ni master alloy or pure nickel, pure copper, Mg-Zr master alloy, Mg-X master alloy or pure X are added in sequence, stirred, and allowed to stand to obtain a melt; (3) Casting: Cooling the melt to 720-740° C. for casting; (4) Homogenization treatment: The alloy is homogenized at 400-450°C for 10-30 hours; (5) Hot extrusion: hot extrusion of the homogenized ingot; (6) The hot extruded bar is subjected to a solution aging treatment to obtain the high-strength and high-plasticity soluble magnesium alloy.

7. The preparation method according to claim 6, characterized in that: In step (2), when the total content of Ni and Cu in the melt is greater than 2%, electromagnetic stirring is added to the melt at a stirring speed of 200 to 300 rpm.

8. The preparation method according to claim 6, characterized in that: In step (3), the casting is die casting or semi-continuous casting.

9. The preparation method according to claim 6, characterized in that: In step (5), the extrusion speed during the hot extrusion is 0.1-3 m / min, the extrusion temperature is 250-400° C., and the extrusion ratio is 10-40:

1.

10. The preparation method according to claim 6, characterized in that: In step (6), the solution temperature is 420-500°C, the time is 5-10 hours, and the aging time is 150-250°C, the time is 1-50 hours.